3D printing of Al matrix composites through in situ impregnation of carbon nanotubes on Al powder. (June 2020) - Geng, Kang; Li, Shaofu; Yang, Y.F.; Misra, R.D.K.
Abstract: A homogenous carbon nanotube (CNT)-Al composite powder used for 3D printing was prepared by in-situ impregnation of carbon nanotubes (CNTs) within Al powder. The use of powder substrates produced the unidirectional gas flow and made the synthesized CNTs bend and encircle on the surface of Al powder. The newly made CNT-Al composite powder thus had a good combination of spherical morphology and uniform dispersion of integrated CNTs. In addition, the high-laser-absorbing CNTs on the surface of Al powder improved the laser absorptivity of pure Al powder through surface chemical modification and surface roughening of Al powder. These advantages not only provided positive printing response including accurate control of geometrical dimensions and absence of metallurgical defects, but also enabled retention of CNTs along the grain boundaries and uniform distribution of Al4 C3 nanorods inside the grains after printing. The printed bulk material from CNT-impregnated Al composite powder exhibited good tensile properties, because of the synergistic strengthening effect from highly efficient load transfer of intergranular CNTs and dispersion strengthening effect of intragranular Al4 C3 nanorods. Graphical abstract: Image 1078